PENGARUH KEPUASAN KERJA, DUKUNGAN ORGANISASIONAL, DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP MOTIVASI KERJA KARYAWAN DI BANK MANDIRI Tbk. - Alit Suputra, Gusti; Manuati Dewi, IG.A.; Adnyana Sudibya, Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.01.TAHUN 2016, 2016)
This study aims is to determine the effect of job satisfaction, organizational support, and transformational leadership style on employee motivation. The sampling method used in ithis study is saturated sampling  or census sampling the determination of  the number of samples from all members of the population. Population of this research is 61 employer. Data were collected using questionnaires and analized  by Multiple Linear Regression Technique. The results show that 1)  job satisfaction significant positive effect on employee motivation, 2) organizational support significant positive effect on employee motivation, 3) transformational leadership style significant positive effect on employee motivation. The result is expected to be a reference for the Indonesian banking industry in particular, Bank Mandiri Branch Veterans in identifying variables that can affect employee motivation in an effort to improve motivation, determine policies related to organizational support, and implementation of transformational leadership style. The highest value of standardized beta coefficients are variable organizational support which has a positive influence and the most dominant influence the motivation of employees at Bank Mandiri Tbk. amounted to 0.395, this means that the level of motivation is strongly influenced by the organizational support
Keywords: Job Satisfaction, Organizational Support, Transformational Leadership Style, Work Motivation